Dynamic performance optimization of two-stage thermoelectric generator: Impact of different geometric leg shapes in each stage - Olao Yair Enciso-Montes de Oca; Miguel Angel Olivares-Robles (Energy Reports, 2024)
This study presents a single-stage and two-stage thermoelectric generator (TEG) with different geometric shapes of the legs (rectangular, trapezoidal, inverted trapezoidal, rhomboid, and hourglass shapes). The various geometric shapes of the legs are combined between the two stages using phase change material (PCM) to cool the generator. The study's objective is to determine the optimal dynamic behavior of the TEG through the geometric design of the legs. The results show the behavior of the efficiency, the generated voltage, and the time it takes for the PCM to melt. The legs of the optimal two-stage system, Rhomboid-Rhomboid (G) and Trapezoidal-Inverted Trapezoidal (B), with a relationship γT=4, reach the best efficiency of 3.88% and 3.9% for the first and second stages, respectively, applying a heat flow of Qh=0.1W. On the other hand, the single-stage rhomboid system achieves the same maximum efficiency as the two-stage rhomboid system (G system), which is 3.9%. The temperature difference of each module is almost the same as that of the single-stage system. However, the voltage generated by the two-stage TEG is higher, and the efficiency remains practically constant compared to the single-stage system, which decreases with time. The effect of PCM's phase change process on TEG performance is analyzed, considering the characteristic heat transfer of PCM.